2021
DOI: 10.3390/s21155215
|View full text |Cite
|
Sign up to set email alerts
|

Damage Detection on a Beam with Multiple Cracks: A Simplified Method Based on Relative Frequency Shifts

Abstract: Identifying cracks in the incipient state is essential to prevent the failure of engineering structures. Detection methods relying on the analysis of the changes in modal parameters are widely used because of the advantages they present. In our previous research, we found that eigenfrequencies were capable of indicating the position and depth of damage when sufficient vibration modes were considered. The damage indicator we developed was based on the relative frequency shifts (RFS). To calculate the RFSs for v… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 40 publications
0
17
0
Order By: Relevance
“…If the fixing is nonideal, the frequency drop is bigger. In prior research, we demonstrated that the superposition principle is valid [26]. For a beam with two cracks, which have position 1 x , and depths 1 a and 2 a , respectively, the frequency drop is calculated as the sum of the two RFS, that is…”
Section:  mentioning
confidence: 97%
“…If the fixing is nonideal, the frequency drop is bigger. In prior research, we demonstrated that the superposition principle is valid [26]. For a beam with two cracks, which have position 1 x , and depths 1 a and 2 a , respectively, the frequency drop is calculated as the sum of the two RFS, that is…”
Section:  mentioning
confidence: 97%
“…If the fixing is non-ideal, the frequency drop is bigger. In prior research, we demonstrated that the superposition principle is valid [ 33 ]. For a beam with two cracks, which have position and , and depths and , respectively, the frequency drop is calculated as the sum of the two RFS, that is …”
Section: Creating the Database For Machine Learning (Ml)mentioning
confidence: 99%
“…By using the method described in the current paper, by employing Equation (11), we have generated training data for developing a damage detection neural network similar to the one presented in [13]. The training data consist of the RFS values for the six transverse vibration modes.…”
Section: Tests Performed Involving Laboratory Experimentsmentioning
confidence: 99%
“…When examining the methods proposed in the literature, we observed that the dependency between the reduction in the size of the crack and the stiffness is rarely considered. In general, the authors limit the study to finding the element in the beam with the lower Young modulus value [13]. When damage detection is applied to trusses, finding the member with the lower Young modulus is usually the target.…”
Section: Introductionmentioning
confidence: 99%